Studi In Silico Senyawa Aktif Asam Jawa (Tamarindus indica L.) Sebagai Antidiabetes Melalui Inhibisi Protein Tyrosine Phosphatase - Tri Setyo Pamungkas; Rosario Trijuliamos Manalu (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2023)
Tamarind leaves (Tamarindus indica L.) are widely cultivated in tropical countries, including Indonesia. Empirically, tamarind leaves are known to have anti-diabetic properties. In this study, an in-silico method was used to test the active compounds found in tamarind leaves (Tamarindus indica L.) as anti-diabetic agents through docking score analysis. The target protein used was Protein Tyrosine Phosphatase (5JNT) which is related to insulin resistance. Glimepiride and native ligand 5JNT were used as reference ligands, while the active compounds of tamarind leaves (Tamarindus indica L.) were used as the test ligands. There were 12 active compounds tested for drug-like properties based on the Lipinski Rule of Five, and 12 compounds met the criteria which were then tested through molecular docking using the PLANTS software. Based on the docking results, there were four compounds that had potential as anti-diabetic agents, namely linalool anthranilate, hexadecanol, pentadecanol, and benzyl benzoate, with docking scores of -85.889, -84.23032, -83.12325, and -81.54821 respectively. Although the docking scores of these compounds exceeded the score of the native ligand 5JNT, they did not exceed the score of the reference ligand glimepiride.